A curricularização da extensão e os desafios para a formação docente - Moraes, Natália Ávila (2021)
There is a need to give greater emphasis to Extension in university education, fostering the principles of teaching-research-Extension inseparability. This discourse is very current and aims to direct universities and the community to the construction of pedagogical proposals that interact more adequately with extension practices. A new term, extension accreditation or extension curricularization, is transforming the pedagogical projects of undergraduate courses and causing changes in teaching practice and, therefore, in the profile of graduates. All this, promoted by reflections that take into account laws and resolutions that are changing the academy with regard to Extension actions. Investigating how Extension is contemplated in the curricula of undergraduate courses in Sciences at UFMT (specifically the degrees in Chemistry, Physics and Biology, Cuiabá campus), was the main objective of this research carried out from the following question: How does Extension curricularization contribute for teacher training? The methodology was supported by the qualitative approach as a case study, focusing on the pedagogical projects of the aforementioned courses and the regulations on the curricularization of the Extension. Meanwhile, the constitution of an educational product was promoted, which was sent as a proposal for a project called Natural Sciences in Extension, evaluated by researchers who are members of the Laboratory of Research and Teaching of Chemistry at UFMT. The results allow us to affirm that the educational product in the format of a proposal, proved to be didactically useful and viable, and that it can help and contribute to the extension practice, as a curricular component, constituting itself as a knowledge producer element, both for the researcher, who gains in knowledge by appropriating the theoretical references and still re-signifies her entire trajectory while she graduates from a degree course, as well as for those to whom the proposal is intended. As mentioned by one of the participants, an extension proposal that is designed and promoted in the interaction between university and society is more likely to succeed and to provoke learning in both the academic and social spheres. From these analyses, it is evident that the University must rethink the concept of curriculum, reflecting on giving a new dimension to the curricula of the courses offered in order to address the issue of inserting these extension credits to understand the extension actions within the Policy that has been built by the Forum of Pro-Rectors for Extension of Brazilian Public Universities, which is still a challenge to be faced.